Decomposing the impact of population growth on environmental deterioration - Gans, Oskar; Jöst, Frank (Discussion paper series, 2005)
The IPAT-model developed by Ehrlich and Holdren is widespread in ecological economics in order to quantify the impact of population growth on environmental deterioration. We comment on this model and extensions proposed by several authors from a theoretical and empirical point of view.
Keywords: Amtsdruckschrift; Statistik; Arbeitspapier; Graue Literatur